Pathology in children with congenital cleft lip and palate. (Texas Journal of Medical Science, 2023)
In children with congenital cleft lip and palate (CCLP), under the influence of endogenous (hereditary) or exogenous (causing disruption of embryogenesis) factors, changes occur in various organs and systems of the body. The commonality of CGN with multiple organ pathologies in the body is explained by the presence of connective tissue dysplasia (CTD). The formation of the multifactorial nature of CGN is realized due to the genetic susceptibility of the organism to the action of externally damaging environmental factors in relation to the fetus. In 75% of children, CRHN is an isolated congenital defect, but it can be combined with other congenital defects. The data presented in the article may be useful for the development of preventive and therapeutic measures, in the prognosis and management of children with this pathology from an individual professional and family perspective.